Expressividade oral na leitura em voz alta: análise de um processo fonoaudiológico com foco nas habilidades leitoras - Tozzo, Ana Paula da Silva (2023)
Introduction: reading aloud by the student is essential to develop reading fluency and requires skill, concentration, and adequate use of oral expressiveness resources. Historically, this practice was used by the school to evaluate their performance in this activity, attributing grades for their clarity and mistakes made. Talking about citizen reading implies thinking about the contributions of other general capacities. However little attention has been paid to this type of activity. Objective: to analyze the effects of a speech therapy process through an intervention focused on oral expressiveness performed with elementary school students. Method: this work was approved by the ethics committee (CAAE 52085521.3.0000.5482). This is a prospective intervention study carried out with 6 students whose performance varied between normal, medium, and weak - two at each level - according to classification and choice of school. All were regularly enrolled in the 5th year of elementary school in a municipal public school in Pontal do Paraná (PR). They participated in a workshop structured in seven meetings where oral expressiveness resources were worked on in a reading-aloud situation. Before and after this intervention, audio-recorded material was collected in which the subjects read a story for later comparison. Parameters of oral expressiveness in reading aloud were worked on, namely, pause, articulation, resonance, intensity, and height, in addition to questions related to reathing, with a focus on pneumophono articulatory coordination. Reading skills were raised during the texts worked. Result: the two subjects with better academic performance, according to the school, made greater use of vocal qualities and oralization of the text. The two with average performance explored vocal qualities, reading skills, and oralization of the text. There was more ease of subjects with greater academic demand in reading skills and oralization of the text. As for the self-assessment, the subjects noticed a difference between the pre- and post-intervention recordings and opted for the second reading. They claimed that they made greater use of intensity, height, and improved speed. Regarding the oralization of the text, the body composed the reading more with emphasis on gestures, body inclination, and less nervousness. Conclusion: the present study showed that this modality of work can make reading more creative and activates resources that collaborate in the appropriation of reading skills